Surgical Tactics of Tumorous Obturation Obstruction of The Colon - Khamdamov Khabibullo Khamdamovich (Genius Journals, 2024)
Purpose of the study is to improve the results and choice of surgical treatment for colon cancer complicated by obstructive colonic obstruction.
Keywords: complicated; improve; results